Neuroinflammation and structural injury of the fetal ovine brain following intra-amniotic Candida albicans exposure. Issue 1 (December 2016) - Ophelders, Daan; Gussenhoven, Ruth; Lammens, Martin; Küsters, Benno; Kemp, Matthew; Newnham, John; Payne, Matthew; Kallapur, Suhas; Jobe, Allan; Zimmermann, Luc; Kramer, Boris; Wolfs, Tim
Abstract Background Intra-amnioticCandida albicans  (C. Albicans ) infection is associated with preterm birth and high morbidity and mortality rates. Survivors are prone to adverse neurodevelopmental outcomes. The mechanisms leading to these adverse neonatal brain outcomes remain largely unknown. To better understand the mechanisms underlyingC. albicans -induced fetal brain injury, we studied immunological responses and structural changes of the fetal brain in a well-established translational ovine model of intra-amnioticC. albicans infection. In addition, we tested whether these potential adverse outcomes of the fetal brain were improved in utero by antifungal treatment with fluconazole. Methods Pregnant ewes received an intra-amniotic injection of 107 colony-forming unitsC. albicans or saline (controls) at 3 or 5 days before preterm delivery at 0.8 of gestation (term ~ 150 days). Fetal intra-amniotic/intra-peritoneal injections of fluconazole or saline (controls) were administered 2 days afterC. albicans exposure. Post mortem analyses for fungal burden, peripheral immune activation, neuroinflammation, and white matter/neuronal injury were performed to determine the effects of intra-amnioticC. albicans and fluconazole treatment. Results Intra-amniotic exposure toC. albicans caused a severe systemic inflammatory response, illustrated by a robust increase of plasma interleukin-6 concentrations. Cerebrospinal fluid cultures were positive forC. albicans in the majority of the 3-dayC. albicans -exposed animals whereas no positive cultures were present in the 5-dayC. albicans -exposed and fluconazole-treated animals. AlthoughC. albicans was not detected in the brain parenchyma, a neuroinflammatory response in the hippocampus and white matter was seen which was characterized by increased microglial and astrocyte activation. These neuroinflammatory changes were accompanied by structural white matter injury. Intra-amniotic fluconazole reduced fetal mortality but did not attenuate neuroinflammation and white matter injury. Conclusions Intra-amnioticC. albicans exposure provoked acute systemic and neuroinflammatory responses with concomitant white matter injury. Fluconazole treatment prevented systemic inflammation without attenuating cerebral inflammation and injury.